THE EFFECT OF IRRIGATION METHODS AND MAGNETIZATION OF WATER ON GROWTH AND YIELD OF SUNFLOWER AND WATER USE EFFICIENCY - & Abdul-Razaq, Yahya (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
This experiment was carried out at the experimental farm of Field Crop Department, College of Agriculture, university of Baghdad, during two spring seasons of 2012 and 2013 to study the response of sunflower cultivar Akmar to irrigation methods, magnetized water technology on growth characteristics, yield and water use efficiency. The experiment was laid out as a split plot in randomized complete block design with three replications. Four irrigation methods were used as main plots, [farrow irrigation (I1), unfixed alternate furrow irrigation (I2), fixed alternate furrow irrigation (I3) and basin irrigation (I4)], while four levels of magnetized water (0, 1000, 2000 and 3000) Gauss were used as sub plot treatments. Results revealed that unfixed alternate furrow irrigation method (I2) did not increase the yield and growth of sunflower for both seasons but it reduces irrigation water by 40%. Yield reached 3.08 and 2.82 ton ha-1 in the two seasons respectively, were as irrigation water reduced from 425 to 255 mm per season in 2012 season and reduced from 364 to 234 mm per season in 2013th season were an increment of water use efficiency (WUE) by 63.5% and 61.4% during growing seasons respectively in comparison with full irrigation treatment (I1). Root dry weight was increased by 4.8 and 7.5%. Results displayed a positive effect of using magnetized irrigation water on all measured traits. Yield was increased by 44.0 to 43.0%, WUE increased by 45.1 to 56.0 %, root dry weight by 8.9 and 8.0%, plant height by 4.7 and 5.3%, number of leaves per plant increased by 7.8 to 4.3%, leaf area by 24.1 % to 25.8 %, stem diameter by 10.2 to 7.9% and total dry weight by 23.9 to 18.6% for both spring seasons of 2012 and 2013 respectively. Interaction relations between experiment treatments were significant in some of studded traits.